(untitled) (INNOVATIVE ECONOMY, 2024)
Shvarchovskyi I.V. ENCOURAGING INNOVATIVE INITIATIVES TO ENTERPRISE PERSONNEL: FOREIGN PRACTICES Purpose. The aim of the article is to systematize approaches to support innovative initiatives of personnel of enterprises formed within the framework of foreign practices. Methodology of research. The study used the method of a systems approach, with the help of which the key approaches to support of innovative initiatives of personnel of high-tech enterprises abroad were classified. Using comparative analysis, the advantages of using certain support practices were identified. Using the induction method, the features of the presented approaches were established from various disparate sources and formulated in the form of systematized complex data. Findings. It has been established that at the current stage of scientific thought in foreign practice, certain approaches have been formed regarding the support of innovative initiatives of the personnel of enterprises: 1) an approach based on organizational support for innovative initiatives of the personnel of Chinese enterprises operating in the field of high technologies. The indicated organizational support is divided into two types: expected moderate material and non-material support (consistent practices of the organization regarding care and appreciation of employees for their influence on its innovative development) and high expected organizational material and non-material support (influences the manifestation of active dedication and creativity); 2) an approach related to attracting creative and talented personnel to work in the company and activating innovative initiatives. The emphasis here is on the effective use of modern digitalization tools and artificial intelligence; 3) an approach to support the innovativeness of personnel, based on the stimulation of team leaders of the work team. In the leading Chinese high-tech companies there is an attractive system of material and non-material support for the initiatives of individuals who show the desire and have the potential for leadership in the field of R&D. Originality. The theoretical provision of the composition of types of support for innovative initiatives of enterprise personnel has gained further development. Practical value. The obtained results of the conducted research can be used in the development of scientific and methodological materials on the specified issues. Key words: support for innovative initiatives of personnel, high-tech enterprises, foreign practices, digitalization, artificial intelligence, R&D, creative and talented personnel, leadership.